Mounting Uncertainties in the Global Trade Order and Korea's Policy Response - Yeongkwan Song (Korea Development Institute (KDI), 2020)
The US-China trade war is propagating uncertainties within the global trade order, weakening global value chains and the WTO system. These uncertainties pose a considerable threat to the Korean economy which is heavily dependent on foreign trade. To tackle this, the Korean government needs to positively consider joining the CPTPP and make efforts to improve the effectiveness and efficiency of policies for the materials and components industries as well as export support.
Keywords: 330; Business Regulation: Sale; Qualification Restriction